The complete typographer : a foundation course for graphic designers working with type. - Hill, Will, 1954- (London : Thames & Hudson, 2010)
Provides an introductory grounding in Typography. This title teaches the essentials for the effective use of type - technical expertise and historical knowledge, an understanding of the functional and aesthetic qualities of different typefaces, and the organization of typographic space.
Previous ed.: Upper Saddle River, N.J.: Prentice Hall, 2005.
Includes bibliographical references and index.
Formerly CIP.
boek